A New Salt‐Baked Approach for Confining Selenium in Metal Complex‐Derived Porous Carbon with Superior Lithium Storage Properties. (16th July 2015) - Li, Xiaona; Liang, Jianwen; Hou, Zhiguo; Zhang, Wanqun; Wang, Yan; Zhu, Yongchun; Qian, Yitai
Abstract : For lithium‐selenium batteries, commercial applications are hindered by the inferior electrical conductivity of selenium and the low utilization ratio of the active selenium. Here, we report a new baked‐in‐salt approach to enable Se to better infiltrate into metal‐complex‐derived porous carbon (Se/MnMC‐B). The approach uses the confined, narrow space that is sandwiched between two compact NaCl solid disks, thus avoiding the need for protection with argon or a vacuum environment during processing. The electrochemical properties for both lithium and sodium storage of our Se/MnMC‐B cathode were found to be outstanding. For lithium storage, the Se/MnMC‐B cathode (with 72% selenium loading) exhibited a capacity of 580 mA h g −1 after 1000 cycles at 1 C, and an excellent rate capability was achieved at 20 C and 510 mA h g −1 . For sodium storage, a specific capacity of 535 mA h g −1 was achieved at 0.1 C after 150 cycles. These results demonstrate the potential of this approach as a new effective general synthesis method for confining other low melting point materials into a porous carbon matrix. Abstract : A new baked‐in‐salt approach to let Se infiltrate into porous carbon is proposed, without the need for a protective argon or vacuum environment. The use of NaCl, which has a higher specific heat capacity than Se, assures an almost constant fabrication temperature, by reducing temperature fluctuations in the system. The Se/C sample exhibits excellent electrochemical performance both in Li–Se and Na–Se batteries. Furthermore, this approach should also be effective for confining other low melting point materials into porous carbon.